2006
DOI: 10.1562/2005-06-20-ra-581
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular Hydrogen Abstraction from Phenols by Aromatic Ketone Triplets†

Abstract: Absolute rate constants for hydrogen abstraction from 4-methylphenol (para-cresol) by the lowest triplet states of 24 aromatic ketones have been determined in acetonitrile solution at 23 degrees C, and the results combined with previously reported data for roughly a dozen other compounds under identical conditions. The ketones studied include various ring-substituted benzophenones and acetophenones, alpha,alpha,alpha-trifluoroacetophenone and its 4-methoxy analog, 2-benzoylthiophene, 2-acetonaphthone, and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 51 publications
5
58
0
11
Order By: Relevance
“…A abstração de hidrogênio fenólico por estados excitados triplete de carbonilas normalmente é mais rápida que aquela observada para toluenos, uma vez que fenóis apresentam tanto uma menor energia de dissociação da ligação O-H, comparada à C-H, quanto um menor potencial de oxidação que toluenos. Assim, o mecanismo da reação de abstração de hidrogênio de fenóis deve ocorrer através da formação inicial de um exciplexo triplete, estabilizado por ligação de hidrogênio, seguido por uma transferência seqüencial de elétron e de próton [17][18][19][20][21][22][23][24][25] . 1,4-diazabiciclo[2.2.2]octano (DABCO) suprime de maneira eficiente (k q =5,5x10 9 L mol -1 s -1 , Tabela 1, Figura 4) o estado excitado triplete de 1,3-indanodiona (1) através um processo de transferência de elétron, levando à formação do ânion radical da dicetona, isto é 4, e do cátion radical derivado da amina (Esquema 2).…”
Section: Resultsunclassified
“…A abstração de hidrogênio fenólico por estados excitados triplete de carbonilas normalmente é mais rápida que aquela observada para toluenos, uma vez que fenóis apresentam tanto uma menor energia de dissociação da ligação O-H, comparada à C-H, quanto um menor potencial de oxidação que toluenos. Assim, o mecanismo da reação de abstração de hidrogênio de fenóis deve ocorrer através da formação inicial de um exciplexo triplete, estabilizado por ligação de hidrogênio, seguido por uma transferência seqüencial de elétron e de próton [17][18][19][20][21][22][23][24][25] . 1,4-diazabiciclo[2.2.2]octano (DABCO) suprime de maneira eficiente (k q =5,5x10 9 L mol -1 s -1 , Tabela 1, Figura 4) o estado excitado triplete de 1,3-indanodiona (1) através um processo de transferência de elétron, levando à formação do ânion radical da dicetona, isto é 4, e do cátion radical derivado da amina (Esquema 2).…”
Section: Resultsunclassified
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The mechanism for this process is now well established and involves the initial formation of a hydrogen-bonded exciplex in the triplet excited state, followed by electron transfer and, subsequently, an ultrafast proton transfer. 4,9-16 DFT calculations clearly showed that for the triplet complex (exciplex) ketone-phenol the hydrogen transfer is predominantly occurring.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The mechanism for this process is now well established and involves the initial formation of a hydrogen-bonded exciplex in the triplet excited state, followed by electron transfer and, subsequently, an ultrafast proton transfer. 4,[9][10][11][12][13][14][15][16] DFT calculations clearly showed that for the triplet complex (exciplex) ketone-phenol the hydrogen transfer is predominantly occurring. 8 The very fast quenching rate constants of triplet carbonyls towards phenols is consequence of both the low reduction potential of the former as well as the low oxidation potential of the later.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations